Farmers’ Adoption of Tobacco Production Technology in Khounkham District, Khammouane Province, Lao People’s Democratic Republic - Chanthavong, Inta; Xayyaphet, Bansack; Phengsavanh, Somxay; Souliya , Oupasoth; Youyabouth, Chandokkham (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The adoption of technology is an imperative factor for economic development. Successful introduction of technology for the developing countries requires thorough understanding of the priorities and concerns from the smallholder of farmers at the grassroots. Thus, the objectives of the study were to study: the farmers’ adoption of tobacco production technology; factors affecting farmers’ adoption of tobacco production technology; and problems and suggestions about tobacco production. Two-stage random sampling technique was used to determine the sample size and the questionnaire was created to collect data from a sample of 182 farmers. Statistical techniques were used descriptive statistics and multiple regression. The result of the research revealed that the farmer’s adoptions on tobacco production technology were all at an average high level ( = 3.62). The factors affecting farmers’ adoption are three factors such as; participation in agricultural training, educational attainment, and the number of laborers in the households. The problems of the tobacco production found were; 1) Soil erosion due to slope areas 2) The costs and inputs for productions were high, particularly labor, fertilizers, and pesticides costs. 3) Tobacco yield was affected by natural disasters for example drought and flooding, and 4). The price of tobacco is quite low. Therefore, the farmers suggested to the concerned agencies to promote and develop tobacco production by the following recommendations; 1) Farmers are encouraged to prioritize education to equip them with necessary knowledge and skills. 2) Farmers should focus more on increasing labor-days for optimal to ensure close supervision of tobacco at all stages to minimize on-field losses. And; 3) Stakeholders should organize more useful seminars and intensive training programs on tobacco farming in order to provide farmers with skills and innovative knowledge to improve the traditional on-field tobacco management practices since most agriculturist depends on tobacco production.